2014
DOI: 10.1161/strokeaha.113.003606
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil Mediates Blood-Flow Redistribution and Neuroprotection After Neonatal Hypoxia-Ischemia

Abstract: The goal of this study was to test the hypothesis that boosting NO-cGMP signaling through PDE-5 inhibition with sildenafil would enhance microcirculatory CBF, reduce ipsilateral Background and Purpose-The best conceivable treatment for hypoxia-ischemia (HI) is the restoration of blood flow to the hypoxic-ischemic region(s). Our objective was to examine whether boosting NO-cGMP signaling using sildenafil citrate, a phosphodiesterase-type 5 inhibitor, could modify cerebral blood flow and reduce lesions in the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 37 publications
1
68
1
Order By: Relevance
“…[41][42][43][44][45] Thus, in the short term, sildenafil may help restore the blood flow to the affected retina. In fact, Charriaut-Marlangue et al 46 demonstrated a blood flow increase in the common carotid artery contralateral to the ligated side after a single administration of intraperitoneal sildenafil immediately following an HI insult in a premature rat model of neonatal HIE. However, in our study, sildenafil was administered with a 12-hour delay and continued for 7 days; thus, a process other than acute vasodilation is likely involved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[41][42][43][44][45] Thus, in the short term, sildenafil may help restore the blood flow to the affected retina. In fact, Charriaut-Marlangue et al 46 demonstrated a blood flow increase in the common carotid artery contralateral to the ligated side after a single administration of intraperitoneal sildenafil immediately following an HI insult in a premature rat model of neonatal HIE. However, in our study, sildenafil was administered with a 12-hour delay and continued for 7 days; thus, a process other than acute vasodilation is likely involved.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][48][49][50][51][52] In a premature rat model of brain injury, sildenafil has been shown to decrease neuronal apoptosis and microglial activation. 46 Because neuronal apoptosis has been shown to peak at 24 hours after HI in the neonatal retina, 2 the sildenafil administered 12 hours after HI may have limited apoptosis and further degeneration by its possible antiapoptotic and anti-inflammatory effects, which have been observed in the adult rat brain. 11,15,48,49,51 Further investigations are needed to determine the exact mechanisms underlying the beneficial effects of sildenafil on retinal function and structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is not clear if sildenafil induces oligodendrogenesis or if it inhibits cell death/apoptosis or both. Myelin protection and oligodendrocyte proliferation have also been demonstrated in ischemic models [147,148], and several studies showed that PDE5-Is inhibit apoptosis in central neurological disease models [122,148,149].…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…In 2014, Charriaut-Marlang et al [148] surgically induced ischemia model in P7 Sprague-Dawley rat pups by occlusion in the right common carotid artery and tested sildenafil. The animals were treated with a single dose of Viagra ® (Pfizer, 10 or 5 mg/kg i.p.).…”
Section: Strokementioning
confidence: 99%